Hubungan Obesitas Dengan Kejadian Hipertensi Pada Remaja - Mawar Eka Putri; Safra Ria Kurniati; Dea Muspratiwi; Evan Agustiar (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Obesity in adolescents can cause various health problems, both physical and psychological. Physical consequences include increased risk of heart disease, hypertension, type 2 diabetes, respiratory problems, bone and joint problems, and the risk of certain cancers. In addition, obesity can also cause psychological problems such as low self-esteem, depression, and anxiety, as well as social problems such as bullying. Hypertension in adolescents is a problem because it will continue into adulthood with a high risk of morbidity and mortality. The increase in obesity is accompanied by an increase in comorbidities that have the potential to become degenerative diseases in the future, such as coronary heart disease, type 2 diabetes and hypertension. The purpose of the study was to determine the relationship between obesity and the incidence of hypertension in adolescents. This study was conducted in the Tanjungpinang Health Center work area on January 10-13, 2025. The study design used a cross-sectional. The population in this study were adolescents in the Tanjungpinang Health Center work area, the sample in this study amounted to 30 people. The hypothesis test used was chi-square. The results showed a relationship between obesity and hypertension in adolescents with a ρ-value of 0.003 (ρ ≤ 0.05). It is hoped that in the future adolescents can control their weight within the ideal range so that the risk of hypertension can be minimized.